Contribuição ao estudo do gênero Echinaster Muller & Troschel, 1840 (Echinodermata: Asteroidea) no litoral brasileiro - Ávila-Pires, Teresa Cristina S. (1982)
383 specimens of Echinaster are studied from 12 localities along Brazilian coast south of the state of Ceará. Besides description of characters, four numerical variables are compared graphically for each locality. The following result was obtained: it was only found E. echinophorus (Lamarck), in the Northeast and E. brasiliensis Müller & Troschel in Southeast and South Brazil. E sentus, E. antonioensis and E. spinulosus when cited from Southeastern and Southern Brazilian coast, are synonymised with E. brasiliensis. E. densispinulosus Tommasi is believed to be a junior synonym of E. brasiliensis and, concerning E. nudus Tommasi, its presence at continental shelf needs confirmation. Occurrence of E. brasiliensis in Northeast Brazil is discussed, as well as situation of the Northern littoral.